MODEL PEMBELAJARAN INQUIRY DALAM PENINGKATAN PRESTASI BELAJAR IPS TERPADU - Susilawati, Samsul (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2015)
General problems faced by most of teacher to promote their learning are how to develop non-conventional learning strategy to motivate their students. It’s difficult to develop learning strategy that can promote student all of competencies, promote student values such a democratic and responsibilities values. It’s also difficult to develop learning strategy that make society as a learning resource. Along with the development of society and the advancement of technology, teachers are required to be more creative in setting up and designing the learning model. Inquiry learning model requires students to think smart, creative, participative, prospective and responsible. Inquiry learning model is believed to be able to change the learning process from teacher centered to student centered learning. This model roles the students become more active while teachers as facilitators and motivators in the learning process.Key words: Inquiry Learning Model